Effect of service to satisfaction and the impact on loyalty of Brimo users - Cika Ramadhanti; Indrawati Indrawati (Institute of Computer Science (IOCS), 2023)
Brimo is one of the digital banks owned by Bank Rakyat Indonesia, which has various features that can help the activities of its users. In banking companies, high-quality service to meet customer needs is a demand in surviving in a competitive business environment. It can be analyzed using the dimensions of the e-servqual. This study aims to analyze service and satisfaction and its impact on Brimo user loyalty by using modified e-servqual dimensions: efficiency, reliability, responsiveness, user-friendliness, personal need, assurance, security, and site organization. Research data collection using questionnaires with purposive sampling techniques obtained 406 respondents who matched the criteria. Data processing is carried out using the structural equation model-partial least squares. The research results, namely reliability, user-friendliness, assurance, security, and site organization have a positive and significant effect on customer satisfaction. Other variables, namely efficiency, responsiveness, and personal need, do not have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on customer loyalty. The implication of this study is that Brimo is advised to improve its user interface to be more well-organized to increase customer satisfaction.